2018
DOI: 10.11646/zootaxa.4382.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Hyloscirtus (Anura, Hylidae) from the Colombian and Venezuelan slopes of Sierra de Perijá, and the phylogenetic position of Hyloscirtus jahni (Rivero, 1961)

Abstract: A new species of Hyloscirtus, belonging to the H. bogotensis species Group, is described from the Venezuelan and Colombian slopes of the Sierra de Perijá. The new species can be readily distinguished from its congeners by the combination of the following characters: mental gland present, disc-shaped and small; ulnar, outer, and inner tarsal folds present; calcar tubercle absent; whitish stripes on external border of upper eyelids and supratympanic folds, longitudinally on the mid-dorsum, on supracloacal fold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,229 publications
(18 citation statements)
references
References 0 publications
5
13
0
Order By: Relevance
“…Our phylogeny is consistent with previous phylogenies of Hyloscirtus (e.g., Almendáriz et al 2014; Coloma et al 2012; Faivovich et al 2005; Rojas-Runjaic et al 2018). The sister clade of the H.larinopygion group appears to be the H.armatus group (e.g., Rojas-Runjaic et al 2018, Duellman et al 2016, herein).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our phylogeny is consistent with previous phylogenies of Hyloscirtus (e.g., Almendáriz et al 2014; Coloma et al 2012; Faivovich et al 2005; Rojas-Runjaic et al 2018). The sister clade of the H.larinopygion group appears to be the H.armatus group (e.g., Rojas-Runjaic et al 2018, Duellman et al 2016, herein).…”
Section: Discussionsupporting
confidence: 92%
“…Four species groups within Hyloscirtus ( H.jahni, H.bogotensis, H.armatus , and H.larinopygion group) were recovered with strong support (posterior probability, pp = 1.0 and bootstrap = 100) in both analysis (Figure 1). However, phylogenetic relationships among these groups were weakly supported (pp < 0.71 and bootstrap < 50), as previously reported (Almendáriz et al 2014; Coloma et al 2012; Guayasamin et al 2015; Rojas-Runjaic et al 2018). The only exception was the strong support found for the clade H.armatus group + H.larinopygion group found in the Bayessian analysis (pp = 0.99).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…We find that difficulty in the manageability of a very large group like Hylidae, also invoked by Duellman et al (2016:5) as justification for their taxonomic changes, is questionable insofar as it means different things to 3 Regarding generic changes introduced by Duellman et al (2016) in Cophomantini Hoffman, 1878, Rojas-Runjaic et al (2018 recentely showed that the recognition of their new genus Colomascirtus (erected despite the cautionary remarks on the taxonomy of Hyloscirtus Peters, 1882by Rivera-Correa et al, 2016 for the former Hyloscirtus armatus and H. larinopygion Groups makes Hyloscirtus as redefined by Duellman et al (2016) paraphyletic, leading them to consider Colomascirtus to be a junior synonym of Hyloscirtus. Faivovich and De la Riva (2006) had explicitly questioned the monophyly of the Hyloscirtus bogotensis Group as defined by Duellman (1972) and Faivovich et al (2005), for which Duellman et al (2016) restricted the genus Hyloscirtus.…”
Section: Recent Taxonomic Changes Involving Ranks In Hylidaementioning
confidence: 75%